New solutions for old problems - Pontillo, Alessandro (Cranfield University, 2018)
3 Minute Thesis presented at the Cranfield Doctoral Network Annual Event, September 2018.Highly flexible structures are now a common scenario in the aeronautic industry due to the adoption of slender and longer wings in order to reduce drag and increase the overall aircraft efficiency. Such configuration brings new challenges as structural dynamics now overlaps flight dynamics. Testing is then more important than ever. The Cranfield BEam Reduction and Dynamic Scaling (BEARDS) programme aims to provide a numerical and experimental tool able to dynamically scale-down a full aircraft and to test it successfully in the wind tunnel. Being able to predict static response along with structure dynamics, allows either universities and industry to mitigate the risk of testing bigger and more expensive models. The presentation will focus on the BEARDS methodology, results obtained from tests already done in the Weybridge wind tunnel and on the future of the programme with the new designed eXperimental Beards (XB-2) model.
Keywords: flight dynamics; 'wind tunnel tests'; 'dynamic scalng'; 'CranfieldDN2018'; 'Aerospace Engineering'; 3MT